2019
DOI: 10.1158/1055-9965.epi-19-0008
|View full text |Cite
|
Sign up to set email alerts
|

Alterations to the Esophageal Microbiome Associated with Progression from Barrett's Esophagus to Esophageal Adenocarcinoma

Abstract: Background: The incidence of esophageal adenocarcinoma has risen dramatically over the past half century, and the underlying reasons are incompletely understood. Broad shifts to the upper gastrointestinal microbiome may be partly responsible. The goal of this study was to describe alterations in the esophageal microbiome that occur with progression from Barrett's esophagus to esophageal adenocarcinoma.Methods: A case-control study was performed of patients with and without Barrett's esophagus who were schedule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 40 publications
4
77
0
Order By: Relevance
“…86,89 Dysplastic BE and EAC are associated with an overall decline in the esophageal microbial diversity 87 and specific changes in taxa, including a rise in Enterobacteriaceae, Akkermansia, and Lactobacillus and a reduction in Veillonella. 83,87,97 A similar decline in microbial diversity has also been observed in patients with dysplastic squamous epithelium. 95 Fusobacterium is both enriched in esophageal squamous cell carcinoma and associated with poor survival, [91][92][93] suggesting a potential role in carcinogenesis.…”
Section: Esophageal Microbiota In Health and Diseasesupporting
confidence: 63%
See 2 more Smart Citations
“…86,89 Dysplastic BE and EAC are associated with an overall decline in the esophageal microbial diversity 87 and specific changes in taxa, including a rise in Enterobacteriaceae, Akkermansia, and Lactobacillus and a reduction in Veillonella. 83,87,97 A similar decline in microbial diversity has also been observed in patients with dysplastic squamous epithelium. 95 Fusobacterium is both enriched in esophageal squamous cell carcinoma and associated with poor survival, [91][92][93] suggesting a potential role in carcinogenesis.…”
Section: Esophageal Microbiota In Health and Diseasesupporting
confidence: 63%
“…80 Alterations in the esophageal microbiome have also been observed with the use of PPIs. [81][82][83] Assessing the microbial composition of the esophagus before and after 8 weeks of PPI therapy, Amir et al found significant changes, including increases in members of Clostridia due to the medication. 81 Whether such changes are specific to PPIs or can be seen with other medications, including other classes of heartburn medications, antibiotics, or immunosuppressants, is unknown but may have important implications for conditions like esophageal candidiasis.…”
Section: Esophageal Microbiota In Health and Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, noxious products from these bacteria, including hydrogen peroxide, may directly inhibit the growth of other bacteria and enable Lactobacillus to dominate in the lower esophagus. 23 A study by Snider et al 32 also showed that microbial diversity decreased in patients with EAC. The proportion of Firmicutes phylum (including Streptococcus) increased in the low-grade dysplasia, as compared to high- grade dysplasia or adenocarcinoma.…”
Section: Esophageal Cancer and Esophageal Microbiomementioning
confidence: 98%
“…The lack of alteration of the microbial community with PPI use is an important finding. Previous studies have shown that patients who develop Barrett’s esophagus have a different microbial community in their esophagus than patients without Barrett’s esophagus [ 28 ]. It is likely that there are factors other than pH and PPI use which cause this conversion of the esophageal mucosa and increased risk for esophageal cancer.…”
Section: Discussionmentioning
confidence: 99%